Protective Barriers and Entrapping Walls: Perceptions of Borders in the Post-Yugoslav Bosnian Diaspora. Issue 3 (3rd July 2017) - Huttunen, Laura
ABSTRACT: This article analyzes the violently changing border regime in the ex-Yugoslavian territories, particularly in Bosnia-Herzegovina, in the 1990s from the point of view of those who lived through the period of transformation. The focus is on the ways in which local people conceived of the borders during this period and how they describe them in textual form in life-stories and poetry. The impact of both violence and (forced) mobility on imaginaries of borders is analyzed in order to understand how the violent transformation of the border regime affects individuals' relationship to the political landscape. The central argument is that such periods of change allow us to see the temporalities and process-like character of borders more clearly. In this particular case the perception of borders changes from non-visible to leaky and insecure and finally to entrapping walls between life and death. Border crossing is seen as an act that changes the status of the individual; simultaneously the violent changes in the border regime change the identities of places in dramatic ways. The case highlights the importance of analyzing the effects of rapid political changes to the bordering processes and to the ways in which variously positioned putative border crossers encounter them.